scientific coffin v / s la epistemic revolution in the education context. (Revista Electrónica REDINE, 2018)
The scientific revolution occurs whenever no explanation is achieved social facts or phenomena within the current paradigm. Building science is not a fortuitous event, in my opinion, an idea might arise and excellent research there occurs or that explanation and argument promote that idea valid knowledge. But from there to consider as a scientific researcher who is starting in the depths of the research is very ambitious. To be a scientist you have to burn stages and much learning. If we remember what points Popper in their worlds to produce knowledge, it is necessary to learn by doing and gradually moving from the perception of the physical world, a personal knowledge through metacognition, so you can learn before making and produce an implicit knowledge. Already in a more mature stage explicit knowledge is produced and socializes in tangible or virtually. A novel research researcher produces free, without attaching producing experience and paradigm. But the reality lived in a university educational environment is that experienced or mature researchers form us as his research assistants in their world (coffin) and when we mature as researchers will be his disciples and therefore we will be part of that normal science Kuhn of mention. So, to paraphrase Kuhn, paradigms are the framework and foundation from which the student is prepared to take part as a member of a scientific community that will work. Progressively skills as an investigator are consolidated into maturity in research. Revolutionary research will produce extraordinary results.
Keywords: research; education paradigm; revolution